2002
DOI: 10.1590/s1677-04202002000200004
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical efficiency in bean plants (Phaseolus vulgaris L. and Vigna unguiculata L. Walp) during recovery from high temperature stress

Abstract: Bean (Phaseolus vulgaris L., cv. Carioca and cv. Negro Huasteco) and cowpea plants (Vigna unguiculata L. Walp cv. Epace 10) were grown in a growth chamber with PPF at leaf level of 200 mumol.m-2.s-1 and air temperature 25 + 1 ºC. The first fully expanded pair of leaves of 12-day-old plants was submitted to high temperature stress (25, 30, 35, 40, 45 and 48 ºC) for 1.5 h. The photochemical efficiency of PSII during recovery was monitored by means of chlorophyll a fluorescence at six different times (0.5, 1, 2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 24 publications
(21 reference statements)
1
20
0
1
Order By: Relevance
“…An increase in F 0 (and a decrease in Fv/ Fm) has been attributed to the physical separation of PS II RC from their associated pigment antenna resulting in blocked energy transfer of the PS II traps, although a part of this phenomenon could possibly reflect the accumulation of the reduced form of Q A¯. In this study F 0 was used as indicator for damage in PS II, associated to LHC II dissociation and blocking the electron transfer in the reductant side of PS II (Costa et al 2002). M 0 showed its maximal rate at 11 AM and 1 PM when Q A¯r eoxidation is inhibited.…”
Section: Resultsmentioning
confidence: 95%
“…An increase in F 0 (and a decrease in Fv/ Fm) has been attributed to the physical separation of PS II RC from their associated pigment antenna resulting in blocked energy transfer of the PS II traps, although a part of this phenomenon could possibly reflect the accumulation of the reduced form of Q A¯. In this study F 0 was used as indicator for damage in PS II, associated to LHC II dissociation and blocking the electron transfer in the reductant side of PS II (Costa et al 2002). M 0 showed its maximal rate at 11 AM and 1 PM when Q A¯r eoxidation is inhibited.…”
Section: Resultsmentioning
confidence: 95%
“…The photochemical activity is also affected by environmental stresses (Van Kooten & Snel, 1990;Maxwell & Johnson, 2000), such as high temperature (Yamane et al, 1997;Costa et al, 2002). Photochemical reactions are linked to the CO 2 fixation process by supplying ATP and NADPH, and are also regulated by alternative electron sinks, such as photorespiration, Mehler reaction and nitrogen reduction (Champigny, 1995;Cornic & Fresneau, 2002;Noctor et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the effect of high temperature (Pastenes & Horton, 1996b;Yamane et al, 1997;Pastenes & Horton, 1999), the photochemical apparatus may also be influenced by high light intensity (Long et al, 1994;Osmond, 1994;Critchley, 1998), which frequently occurs around noon when air temperature and vapor pressure deficit are elevated. Concerning the effects of elevated air temperature in bean plants, Pastenes & Horton (1996b) and Costa et al (2002) observed that the susceptibility of photosynthetic apparatus depends on studied genotype. Therefore, bean cultivars show different physiological responses when submitted to the same changes in air temperature and vapor pressure deficit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Altas temperaturas podem afetar direta e indiretamente as trocas gasosas, tanto por promover alterações na condutância estomática, quanto pelo fato de provocar mudanças e desarranjo no aparato fotossintético, causando estresse (MAXWELL; JOHNSON, 2000;COSTA et al, 2002;RIBEIRO et al, 2004;SAGE;KUBIEN, 2007). Segundo Wise et al (2004), danos diretos ao aparato fotossintético podem ser ocasionados por altas temperaturas por provocarem alterações nas membranas dos tilacoides, alterando a organização estrutural e as propriedades físico-químicas.…”
Section: Introductionunclassified